The Lecturers' Perception of EMI Training with Multimodal and Interactive Teaching - Sri Lestari; Issy Yuliasri; Sri Wuli Fitriati; Frimadhona Syafri (Universitas Negeri Semarang, 2023)
Based on the evaluation of the implementation of English Medium Instruction (EMI) Class since 2021-2022 at several departments of a private university in East Java, it can be found that content lecturers’ challenge is how to engage students and facilitate students in understanding the material. Therefore, English specialists or lecturers held EMI lecturer training purposed to content subjects who teach in EMI classes. This study offers an overview of how a private university's EMI training program was designed. Some of the steps taken in this process are as follows: introducing EMI implementation (teaching methodology, the use of multimodal and interactive teaching), training, and content subject practicing or teaching demonstration. This study was done by analyzing EMI lecturers’ attitude toward EMI and their perceptions after they participated in joining the training. The findings showed that EMI training is very beneficial for content subjects to boost and improve their quality in the teaching process.